2022
DOI: 10.1038/s41598-022-04899-4
|View full text |Cite
|
Sign up to set email alerts
|

Iterative data-driven forecasting of the transmission and management of SARS-CoV-2/COVID-19 using social interventions at the county-level

Abstract: The control of the initial outbreak and spread of SARS-CoV-2/COVID-19 via the application of population-wide non-pharmaceutical mitigation measures have led to remarkable successes in dampening the pandemic globally. However, with countries beginning to ease or lift these measures fully to restart activities, concern is growing regarding the impacts that such reopening of societies could have on the subsequent transmission of the virus. While mathematical models of COVID-19 transmission have played important r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…We estimate the following parameters, including the probability of transmission per contact and the contact rate in each stage, by using a Monte-Carlo-based Bayesian modeling framework [ 37 , 38 ]. We sample 100,000 parameter vectors from the uniform prior distribution (Additional file 1 : Table S1), and we choose the 1000 best-fitting parameter vectors based on the modified normalized mean square error (NMSE) indicator by comparing data and model predictions of cumulative confirmed cases and cumulative isolated individuals.…”
Section: Methodsmentioning
confidence: 99%
“…We estimate the following parameters, including the probability of transmission per contact and the contact rate in each stage, by using a Monte-Carlo-based Bayesian modeling framework [ 37 , 38 ]. We sample 100,000 parameter vectors from the uniform prior distribution (Additional file 1 : Table S1), and we choose the 1000 best-fitting parameter vectors based on the modified normalized mean square error (NMSE) indicator by comparing data and model predictions of cumulative confirmed cases and cumulative isolated individuals.…”
Section: Methodsmentioning
confidence: 99%
“…The model is calibrated using publicly available surveillance data of daily new reported cases and deaths, daily hospitalized and ICU cases in Toronto, Ontario, and Canada from January 1 to February 9, 2022 ( City of Toronto, 2022a , 2022b ; Government of Canada, 2022 ; Public Health Ontario, 2022 ). The proportion of nHRS mild symptomatic infections conducting self-testing and PCR testing, the transmission risk, the proportion of hospitalized, ICU and deaths from ICU are estimated using a Monte-Carlo-based Bayesian melding framework ( Newcomb et al, 2022 ) and are reported in Table S6 . The estimations are based on a forwarding weekly time window to capture in a timely fashion the changes in transmission risk and severity.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, while some workers have highlighted the difficulty of anticipating and accommodating novel, unknown, or previously unsuspected changes in the drivers of future viral transmission to allow the making of reliable long-term projections by models [ 10 , 11 ], others have pointed to the value of these models as tools for being able to integrate information on the diverse structures and processes related to transmission dynamics in order to propagate forecasts that are more accurate than predictions afforded by common sense alone [ 12 , 23 ]. Such assessments have also, for example, pinpointed the need for continual model refinement and for the use of data for making predictions to counter the effects of changes in local risk factors [ 12 , 14 , 24 ]. These studies ultimately suggest that, as for other studies investigating socio-ecological futures, the better use of models for forecasting the plausible futures that could be followed by the pandemic is to combine simulations within a scenario framework in order to focus on explorations of possible trajectories in the evolution of the system as a result of changes predicted for key drivers rather than employing them to make precise predictions about the extent or duration of disease burdens [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%